Austalis, a new genus of flower flies (Diptera: Syrphidae) with revisionary notes on related genera - Thompson, F. Christian (Zootaxa, 2003)
A new genus and species of flower flies are described from the Australian biotic region (Austalis Thompson & Vockeroth, type Eristalis resolutus Walker; Austalis rhina Thompson (Solomon Is.)). A key is provided to the groups of the subtribe Eristalina, along with nomenclatural notes and checklist of genus-group names. Five genus-group names and 1 species-group name are synonymized (Pseudomeromacrus Li, 1994 = Eristalinus (Merodonoides Curran, 1931)); Cryptoeristalis Kuznetzov 1994 = Eristalis (Eoseristalis Kanervo, 1938)); Paramesembrius Shiraki 1930, Klossia Curran, 1931 & Catacores Hull, 1944 = Kertesziomyia Shiraki, 1930; Eristalis maritima Hull, 1945 = Austalis resoluta (Walker, 1858)).